2020
DOI: 10.1007/s10639-019-10092-4
|View full text |Cite
|
Sign up to set email alerts
|

Fresh perspectives on TPACK: pre-service teachers’ own appraisal of their challenging and confident TPACK areas

Abstract: The present study is an extension of studies that measure pre-service teachers' Technological Pedagogical Content Knowledge (TPACK) confidence. It provides new perspectives on pre-service teachers' TPACK by shifting the focus to concrete concerns and strengths indicated by pre-service teachers. The target group consists of a cohort of firstyear pre-service teachers (N = 86) from a Finnish university. The data used in this study were 86 lesson plans with integrated technology written by first-year pre-service t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 25 publications
1
54
0
7
Order By: Relevance
“…Nonetheless, the integration and development of multiple forms of knowledge in pedagogy, subject matter, and technology are cognitively demanding. Valtonen et al highlighted that preservice teachers had concerns about their pedagogical knowledge and technological pedagogical knowledge, especially among first-year preservice teachers [25]. So and Kim, on the other hand, reported that preservice teachers found it difficult to craft authentic problems to engender student-centric learning [26].…”
Section: Learning By Designing To Develop Teachers' Tpackmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the integration and development of multiple forms of knowledge in pedagogy, subject matter, and technology are cognitively demanding. Valtonen et al highlighted that preservice teachers had concerns about their pedagogical knowledge and technological pedagogical knowledge, especially among first-year preservice teachers [25]. So and Kim, on the other hand, reported that preservice teachers found it difficult to craft authentic problems to engender student-centric learning [26].…”
Section: Learning By Designing To Develop Teachers' Tpackmentioning
confidence: 99%
“…The work of creating a STEMQuest, as illustrated here, involves complex reasoning with heavy reference to students, who were the target users of the design. It is essentially an effort to create contextualized knowledge [24,25].…”
Section: Tpack As a Complex Student Learning-focused Designmentioning
confidence: 99%
“…General confidence and comfort using technology includes the state of being comfortable in effectively integrating technology into teaching (Hogarty et al 2003). A number of research findings justified that comfort level with technology is associated with technology use (e.g., Valtonen et al 2020; Spiteri and Rundgren 2020; Anderson and Putman 2020). Bebell et al (2004) provided evidence on the positive and moderately strong direct effect of confidence with technology on technology use.…”
Section: Confidence In Using Technology and Technology Usementioning
confidence: 99%
“…High-quality information communication technology (ICT) has been a vital infrastructure for governments who wish to sustain regular education activities during the pandemic [5]. Although these new technologies create new opportunities for learning, they also present challenges for teachers [6]. Teachers are expected to acquire new content and pedagogy-related knowledge and develop new technical skills to offer effective and meaningful instruction [7,8].…”
Section: Introductionmentioning
confidence: 99%